2021
DOI: 10.1038/s41598-021-89382-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of contact angle of spray solution on leaf surfaces with weed control

Abstract: The weeds are important in agricultural and livestock areas because these plants can cause several damages, especially in the yield. The herbicide pulverization for weed control is the most used, but the efficiency of the control can be dependent the several factors, for example, the correct chose the herbicide and the mixture or not with adjuvant. This study aimed to evaluate the contact angle of herbicide solution droplets associated with adjuvant when deposited on the leaf surface of different weed species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…PT exhibited the best wettability behavior, followed by GOEO and MO. However, it was previously reported that smaller contact angles of the pesticide solution might lead to a higher rate of plant poisoning [34]. Organosilicone surfactants may not be safe, as they are toxic to bees [35].…”
Section: Discussionmentioning
confidence: 99%
“…PT exhibited the best wettability behavior, followed by GOEO and MO. However, it was previously reported that smaller contact angles of the pesticide solution might lead to a higher rate of plant poisoning [34]. Organosilicone surfactants may not be safe, as they are toxic to bees [35].…”
Section: Discussionmentioning
confidence: 99%
“…The data were pooled together for analysis because of the lack of a significant interaction between treatment by year. In the bio‐assay studies, the dry weight for johnsongrass, Y , was nonlinear‐regressed over the doses of trifloxysulfuron‐sodium, X , using the four‐parameter logistic model of Y = (( D – C )/(1 + exp ( B (log X ) – logED 50 )) + C in R software 38 . Here, D and C are the maximum and minimum asymptotes of Y , respectively, ED 50 is an effective dose resulting in a 50% control, and B is the slope of the sigmoidal‐shaped curve around ED 50 (curves not shown).…”
Section: Methodsmentioning
confidence: 99%
“…In the bio-assay studies, the dry weight for johnsongrass, Y, was nonlinear-regressed over the doses of trifloxysulfuron-sodium, X, using the four-parameter logistic model of Y = ((D -C)/(1 + exp (B(logX) -logED 50 )) + C in R software. 38 Here, D and C are the maximum and minimum asymptotes of Y, respectively, ED 50 is an effective dose resulting in a 50% control, and B is the slope of the sigmoidal-shaped curve around ED 50 (curves not shown). The standard errors of ED 50 at ⊍ = 0.05 were estimated and used to separate the ED 50 values.…”
Section: Statistical Analysis Of Datamentioning
confidence: 99%
“…For example, plants of C. truncata, S. oleraceus, and C. bonariensis when exposed to water stress showed certain symptoms, such as reduced plant height and leaf surface area, altered leaf position or angle, and stunted growth or reduced biomass production, and leaf folding (i.e., C. truncata). These morphological features related to leaf surface characteristics, especially leaf architecture (e.g., leaf area and angle), as well as height, in relation to the spray nozzle, directly influence the amount of herbicide spray droplet deposition and retention on the leaf surface [47][48][49]. In addition, water-deficit conditions increase leaf cuticle thickness, as observed in our study, alter the epicuticular wax composition, and increase total wax content [50], which can inhibit the absorption and penetration of post-emergent herbicides, such as glyphosate [51].…”
Section: Impact Of Soil Moisture Variations On Weed Morpho-physiology and Growthmentioning
confidence: 99%